Project method as an effective method of teaching and educating students of technical universities - Mantrova, M.S.; Tleumbetova, D.B.; Ivanova, S.A.; Dokuchaeva, N.V. (KSU Publ., 2020)
The article considers the project method as one of the effective means of training and education of a fully developed, independent, initiative person. The article describes the pedagogical value of using project activities in teaching Russian to students of technical universities. It is shown that using this method at Russian language classes reflects the main modern principles of teaching. They contribute to forming communicative skills and increasing motivation of Russian language teaching. The paper is focused on developmental teaching models based on individual characteristics of a person. The authors describe the personal experience of using a practice-oriented project in the classroom of the Russian language and offer it as a productive way to develop creative independence.
Жобалық əдіс оқытудың тиімді тəсілі арқылы техникалық жоғары оқу орындарының студенттеріне білім беру
Метод проектов как эффективный метод обучения и воспитания студентов технических вузов
Keywords: project-method; interactive form of teaching; professionally oriented teaching of Russian language; principle of teaching